Analyzing and improving the thermal performance of road network weighing stations through measurements and CFD modeling - Mohammadreza Tohidi; Jean Rouleau; Louis Gosselin (Case Studies in Thermal Engineering, 2025)
Weighing stations ensure the safety and durability of road infrastructures. In cold climates, weighing stations are heated to melt accumulated snow and maintain an adequate operating temperature, resulting in significant energy consumption. The objective of this work is to understand the heat transfer and airflow within weighing stations and identify potential improvements. A CFD model was developed and validated, based on measurements in a weighing station in Quebec City, Canada. Then, three performance metrics were defined to assess thermal uniformity inside the pit, the heat flux available for snow melting, and the amount of heat losses. A parametric study was performed by varying the heater configuration and capacity, as well as the airtightness of the pit, to identify the most influential variables. Results showed that the heat losses due to airflow through the different gaps in the station were dominant, representing around 54 % of the heat input in the current situation. Adopting a new configuration (more heaters of smaller capacity) and improving airtightness significantly improved thermal performance under simulated conditions. The methods and results from this paper are useful to engineers who design, maintain, operate and renovate weighing stations and other similar heat transfer systems.